2017
DOI: 10.1080/13548506.2017.1361038
|View full text |Cite
|
Sign up to set email alerts
|

High fatigue and its associations with health and work related factors among female medical personnel at 54 hospitals in Zhuhai, China

Abstract: The present study aimed to investigate the prevalence of fatigue and determine factors associated with fatigue in female medical personnel. Based on a cross-sectional study, a total of 1608 female medical personnel at 54 hospitals in Zhuhai, China were recruited by a multistage stratified cluster sampling method. The Symptoms Checklist-90-Revised and Chalder Fatigue Scale were used to assess psychiatric symptoms and fatigue, respectively. Data regarding demographic, health, and work related variables were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
40
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 41 publications
6
40
1
4
Order By: Relevance
“…This cross-sectional research investigated the level of fatigue among 1,104 physicians in Liaoning province, China. The result of the fatigue assessment in this study was 7.96 ± 3.95 (mean ± SD), and it was slightly higher than the score from medical personnel in Zhuhai (mean ± SD: 7.29 ± 3.24), a big city in China (3). Physicians in the study denoted higher levels of fatigue than did the scientific and technical personnel (mean ± SD: 7.28 ± 3.37) (50).…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…This cross-sectional research investigated the level of fatigue among 1,104 physicians in Liaoning province, China. The result of the fatigue assessment in this study was 7.96 ± 3.95 (mean ± SD), and it was slightly higher than the score from medical personnel in Zhuhai (mean ± SD: 7.29 ± 3.24), a big city in China (3). Physicians in the study denoted higher levels of fatigue than did the scientific and technical personnel (mean ± SD: 7.28 ± 3.37) (50).…”
Section: Discussioncontrasting
confidence: 64%
“…According to a survey among general working population in 2018, the rates of fatigue for sedentary workers and physical workers were 17.0 and 38.9%, respectively (2). In reality, fatigue is a longstanding problem within the health-care occupations in many countries, such as China, the United States, the United Kingdom, and Australia, and especially among physicians (3)(4)(5)(6)(7). O'Donnell's research suggested that nearly half of physicians (45.4%) are extremely fatigued (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy might be explained by the different de nitions of fatigues, diverse assessment tools, inconsistent cut-off points and so forth. For instance, Cai et al [50] employed a score of 4 on a 11-item fatigue scales as the cut-off point to de ne the occurrence of fatigue, while O'Donnell et al [46] measured fatigue through only one question via selfassessment of average level of fatigue during the previous week. These differences might be attributed to the different prevalence of fatigue among HCWs.…”
Section: Discussionmentioning
confidence: 99%
“…, while people who have undergone quarantine tend to be aware of the fear and risk perceptions (Tracy et al, 2009;Van Bortel et al, 2016). Based on the Symptom Checklist-90 (SCL-90), research groups used to analyze the psychological impact of the epidemic outbreak on medical staff or survivors (Cai et al, 2017;Ji et al, 2017;Li et al, 2015;Tanaka et al, 2016). So far, only limited researches have analyzed the psychological symptoms and experiences of people during the COVID-19 without the SCL-90 (Qiu et al, 2020;Wang et al, 2020;Yang et al, 2020).…”
mentioning
confidence: 99%